2015
DOI: 10.1063/1.4905690
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial nucleation behavior of inkjet-printed 6,13 bis(tri-isopropylsilylethynyl) pentacene on dielectric surfaces

Abstract: The performance of organic thin film transistors (OTFTs) is heavily dependent on the interface property between the organic semiconductor and the dielectric substrate. Device fabrication with bottom-gate architecture by depositing the semiconductors with a solution method is highly recommended for cost-effectiveness. Surface modification of the dielectric layer is employed as an effective approach to control film growth. Here, we perform surface modification via a self-assembled monolayer of silanes, a spin-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Secondly, the PVP-coating is intact and therefore a smooth interface with the semiconductor persists, which can reasonably lead to enhanced fieldeffect mobility, although the inferior steepness of the subthreshold slope still indicate a poor interface quality. A potential solution via interfacial nucleation on hydrophobic surfaces has been proposed recently [27].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the PVP-coating is intact and therefore a smooth interface with the semiconductor persists, which can reasonably lead to enhanced fieldeffect mobility, although the inferior steepness of the subthreshold slope still indicate a poor interface quality. A potential solution via interfacial nucleation on hydrophobic surfaces has been proposed recently [27].…”
Section: Discussionmentioning
confidence: 99%
“…(c) AFM images of inkjet-printed TIPS-pentacene thin films on SiO 2 /Si substrates by PETS, PTS, PVP coating and UV-ozone treatment. Reprinted with permission from ref . Copyright 2015 AIP Publishing.…”
Section: Printed Tfts On Rigid Substratementioning
confidence: 99%
“…Organic small molecular semiconductor is normally processed by thermal deposition because of its insolubility, such as pentacene, phthalocyanine compounds. Recently, more and more soluble organic small molecular semiconductors have been synthesized via introducing suitable soluble groups for printed electronics, for example, 2,7-dioctyl[1]­benzothieno­[3,2- b ] benzothiophene (C8BTBT) and [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), as shown in Figure b. , The group 6,13-bis­(triisopropyl-silylethynyl) (TIPS) is added into pentacene, it could form a excellently soluble, high-performance TIPS-pentacene. , For fabricating TIPS-pentacene thin film with homogeneity thickness and high-quality morphology via inkjet printing, surface energies were tuned via SAM, ultraviolet (UV)-ozone treatment and a polymeric dielectric (Figure c) . Wang et al demonstrated that the crystal growth of TIPS-pentacene could be controlled by inkjet printing, in which crystal orientation of TIPS-pentacene was adjusted by surface-modified Au because there is a slightly higher dispersive surface energy than the dielectric substrate .…”
Section: Printed Tfts On Rigid Substratementioning
confidence: 99%
See 2 more Smart Citations